Study of anaemia in type 2 diabetes mellitus - Kaushik, Deepali; Parashar, Raman; Malik, Praveen K. (International Journal of Research in Medical Sciences, 2018)
Background: Anaemia is increasingly recognized entity in the patients with diabetes mellitus and constitutes an additional burden in patients. The prevalence of anaemia in the patients with diabetes is two or three times higher than in patients with comparable renal impairment and iron stores in the general population. As India is foreseen a diabetic capital of the world, it becomes imperative to recognize co-morbidities such as anaemia at the earliest. Hence this study is being conducted with the aim to determine the prevalence and various causes of anaemia in diabetics. Methods: After obtaining informed written consent, all diabetics patients were subjected to detailed history, through clinical examination and investigation with CBC, Renal function test including creatinine clearance. The difference of mean between anaemic and non anaemic diabetic patients was evaluated by unpaired student t test. Finally, correlation between the level of haemoglobin and index of renal damage (albumin-creatinine ratio) was accessed by Pearson correlation. Statistical software of SPSS 10 ver. and EXCEL (office 9) was used to analyse the data. Results: In the present study, nearly two third patients of type 2 diabetes mellitus were anaemic. The maximum number of anaemic patients with type 2 diabetes mellitus had microcytic hypochromic type of anaemia. Conclusions: It is therefore concluded that anaemia is a prevalent finding in patients with type 2 diabetes mellitus and represents significant unrecognised burden. The anaemia may be attributed to variable contribution of iron deficiency state and chronic inflammation as result of the disease itself.